Exploring the Innovative Ideas on Service Industry - Tambunan, Damelina Basauli; Napitupulu, Alfons Manuel P.M.; Hartono, Wendra (International Business Management - Universitas Ciputra, 2023)
This study aims to get service innovation ideas for micro, small and medium scale companies (MSMEs) in the service industry, specifically for law office service companies. For this purpose, data was collected using a focus group discussion (FGD) approach which was attended by 30 legal practitioners as informants, to find service innovation ideas in legal service-based companies. The sample was selected using a purposive sampling method with the criteria of having worked at a legal services company for at least 3 years, considering the need for innovation in running a business. This criterion was confirmed through initial interviews with informants. Data is analysed using content analysis. The results of this study indicate that the proposed innovation idea is closely related to the use of technology such as the use of online platforms to promote and even conduct legal consultations; document processing automation technology, an application that functions as a reminder of the schedule, either the schedule for hearing in court or the schedule for uploading the required documents. In addition, collaboration is also needed to generate innovative ideas, both for the development of digital platforms or ecosystems as well as collaboration with other stake holders such as prospective clients and employees to formulate service improvements and management of law office services